2005
DOI: 10.1158/1078-0432.ccr-05-1335
|View full text |Cite
|
Sign up to set email alerts
|

Reveromycin A Inhibits Osteolytic Bone Metastasis of Small-Cell Lung Cancer Cells, SBC-5, through an Antiosteoclastic Activity

Abstract: Purpose: The purpose of this study was to determine therapeutic effect of a novel antibiotic, reveromycin A, against osteolytic bone metastasis of human small cell lung cancer (SBC-5) cells. Results: Reveromycin A induced apoptosis specifically in osteoclasts in vitro. Although reveromycin A did not inhibit SBC-5 cell proliferation, it suppressed the expression of parathyroid hormone^related peptide. Intravenous inoculation of SBC-5 cells in natural killer cell^depleted severe combined immunodeficient mice pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…This finding is consistent with our previous reports on PTHrP antibody alone (14) and reveromycin A (28). Using a breast cancer model, however, we found that zoledronic acid suppressed lung and liver metastases and prolonged overall survival (31), and a recent clinical trial showed that zoledronic acid inhibited visceral metastases and prolonged survival of patients with breast cancer (32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with our previous reports on PTHrP antibody alone (14) and reveromycin A (28). Using a breast cancer model, however, we found that zoledronic acid suppressed lung and liver metastases and prolonged overall survival (31), and a recent clinical trial showed that zoledronic acid inhibited visceral metastases and prolonged survival of patients with breast cancer (32).…”
Section: Discussionsupporting
confidence: 92%
“…This is supported by our findings, showing that PTHrP antibody and/or zoledronic acid did not directly inhibit the proliferation of SBC-5 cells in vitro and in vivo and that treatment with PTHrP antibody and/or zoledronic acid decreased the number of osteoclasts and increased the number of apoptotic tumor cells in bone lesions. Similar results have been observed by treatment of bone metastatic lesions with reveromycin A, an inhibitor of isoleucyl-tRNA synthesis that efficiently induces the apoptosis of osteoclasts (28). The mechanism by which these agents induce tumor cell apoptosis without affecting the number of proliferating tumor cells is unknown at present.…”
Section: Discussionsupporting
confidence: 71%
“…One of the advantages of our metastasis models is that therapeutic efficacy can be evaluated in multiple organs simultaneously (22)(23)(24). We found that E7080 showed therapeutic effects in almost all organs evaluated.…”
Section: Discussionmentioning
confidence: 91%
“…Intravenous inoculation of the SCLC cell line, SBC-5, into NK cell-depleted SCID mice has been shown to produce experimental metastases within 35 days (22)(23)(24). These metastatic lesions were located primarily in the liver where some were greater than 2 mm in diameter.…”
Section: E7080 Suppression Of Enlargement Of Metastases Of Lung Cancementioning
confidence: 99%
“…Elucidation of the mechanisms underlying bisphosphonate activity, especially the identification of target proteins, has led to a deep understanding of osteoclast function (4). In addition, many naturally occurring small molecules have been reported to inhibit the differentiation and function of osteoclasts (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%